Mischodon zeylanicus Thwaites (Euphorbiaceae) - A Rare Tree Species New to Andaman Islands - Chakrabarty, T.; Balakrishnan, N. P. (Rheedea, 2005)
Mischodon zeylanicus Thwaites, endemic to Sri Lanka and Penisular India, is reported from Andaman Islands.